2004
DOI: 10.7326/0003-4819-140-10-200405180-00008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Rosiglitazone in HIV Lipodystrophy

Abstract: The authors demonstrated positive effects of rosiglitazone on lipoatrophy; insulin sensitivity; and metabolic indices, including adiponectin levels, in HIV-infected patients with lipoatrophy and insulin resistance. Peroxisome proliferator-activated receptor-gamma agonists may correct the metabolic abnormalities associated with disrupted adipogenesis in this population. Further studies must determine the clinical utility of such agents in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
134
10
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(154 citation statements)
references
References 52 publications
7
134
10
3
Order By: Relevance
“…Regarding fat redistribution the initially encouraging results reporting a beneficial effect of rosiglitazone in body fat gain [129,130] were not seen during two other studies including a recent larger (n=108) placebo controlled study [131] evaluating rosiglitazone in lipoatrophic HIV patients [131,132] . This has led to the speculation that rosiglitazone may exert its insulin sensitizing effects without increasing the subcutaneous adipose tissue mass [132] .…”
Section: Therapeutic Implications Of the Adipokine Rolementioning
confidence: 93%
See 1 more Smart Citation
“…Regarding fat redistribution the initially encouraging results reporting a beneficial effect of rosiglitazone in body fat gain [129,130] were not seen during two other studies including a recent larger (n=108) placebo controlled study [131] evaluating rosiglitazone in lipoatrophic HIV patients [131,132] . This has led to the speculation that rosiglitazone may exert its insulin sensitizing effects without increasing the subcutaneous adipose tissue mass [132] .…”
Section: Therapeutic Implications Of the Adipokine Rolementioning
confidence: 93%
“…Indeed rosiglitazone has been shown to improve insulin resistance in patients with HIV associated metabolic syndrome, however at the expense of increased triglyceride and cholesterol concentrations [129][130][131][132] . Regarding fat redistribution the initially encouraging results reporting a beneficial effect of rosiglitazone in body fat gain [129,130] were not seen during two other studies including a recent larger (n=108) placebo controlled study [131] evaluating rosiglitazone in lipoatrophic HIV patients [131,132] .…”
Section: Therapeutic Implications Of the Adipokine Rolementioning
confidence: 99%
“…Although insulin levels improved in both studies, subcutaneous fat did not increase. In contrast, Hadigan et al [23] performed a randomized, placebo-controlled study of HIV-infected patients with insulin resistance and fat atrophy. Hadigan et al demonstrated improved insulin sensitivity using the hyperinsulinemic euglycemic clamp procedure and a 24% increase in mid thigh extremity fat as determined by cross-sectional CT scan.…”
Section: Prevalence Of Impaired Glucose Tolerance and Diabetes Mellitusmentioning
confidence: 99%
“…In addition, adiponectin increased significantly, as also shown by Carr et al [22] . Of note, rosiglitazone was associated with an increase in LDL in the three randomized studies performed to date [21][22][23] . This effect has been previously demonstrated in non HIV-infected patients receiving thiazolidinediones and may be improved with use of other agents including pioglitazone, or in combination with lipid lowering therapy.…”
Section: Prevalence Of Impaired Glucose Tolerance and Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation